1985
DOI: 10.1007/bf00442298
|View full text |Cite
|
Sign up to set email alerts
|

Infant sleep apnea profile: preterm vs. term infants

Abstract: By means of polygraphic sleep recording, the sleep apnea profile with respect to the number and duration of inactive, obstructive and mixed apneic episodes as well as periodic breathing has been investigated in infants born preterm at 40, 52 and 64 weeks conceptional age and compared to that of term infants. At 40 weeks preterm infants showed significantly more apnea and periodic breathing compared to term infants. The difference was essentially due to obstructive and mixed apnea in non-REM sleep. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
2
6

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
5
35
2
6
Order By: Relevance
“…1,2,[8][9][10][11]14 Most previous studies were however done on small groups of infants and some studies did not differentiate obstructive from mixed events. 4,8,10,11,14 In the present report, obstructive apneas were almost twice as frequently found than mixed apneas.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…1,2,[8][9][10][11]14 Most previous studies were however done on small groups of infants and some studies did not differentiate obstructive from mixed events. 4,8,10,11,14 In the present report, obstructive apneas were almost twice as frequently found than mixed apneas.…”
Section: Discussionsupporting
confidence: 48%
“…The decrease in apnea frequency with age was also found in several studies, 4,10,11,14,19,21,22 but was not reported by all authors. Guilleminault et al reported an increase in obstructive and mixed apneas during night-time sleep at six weeks of age.…”
Section: Discussionmentioning
confidence: 64%
“…Second, PB occurs during both quiet sleep and active sleep in preterm infants; however, it is largely confined to active sleep in term infants (7,14,(26)(27)(28). Although Barrington et al (14) reported that PCD was not significantly influenced by sleep state in term infants, the higher amount of PB occurring in quiet sleep coupled with longer PB episodes in preterm infants compared to term infants suggests that sleep state could influence PCD variability, especially in light of the sleep state-dependent changes in respiratory control system characteristics which occur in both adults and infants (29).…”
Section: Glotzbach Et a L Conceptional Age (Wk)mentioning
confidence: 99%
“…PB comprises <2% of the respiratory pattern in most normal infants during the first months of life (1)(2)(3), and occurs more frequently and in higher amounts in preterm infants (4)(5)(6)(7)(8). PB may therefore reflect an immaturity of developing respiratory control system elements which does not normally indicate any abnormalities or pathology; however, elevated amounts of PB have been reported in some infants "near-miss" for SIDS and in some SIDS victims (9-1 3).…”
mentioning
confidence: 99%
“…1 Preterm infants have significantly more PB when they reach term than infants who are born at term. 2 Hypoxia has been associated with an increased incidence of PB, 3 and PB by itself may cause episodes of hypoxemia. 4 We are unaware of any study that has reported on the pattern of oxygenation in preterm infants who have significant PB.…”
Section: Introductionmentioning
confidence: 99%